Responder
**Solutions:**
- **a)** \( x = 0 \) and \( x = 2 \)
- **b)** \( x = 9 \) and \( x = -9 \)
- **c)** \( x = 4 \) and \( x = -3 \)
- **d)** \( x = 7 \) and \( x = 2 \)
- **e)** \( x = \frac{1}{27} \) and \( x = 8 \)
- **f)** \( x = 16 \)
Solución
Sure! Let's solve each of the quadratic equations by factorization step by step.
---
### **a) \( 3x^{2} - 6x = 0 \)**
**Step 1: Factor out the greatest common factor (GCF).**
The GCF of \( 3x^{2} \) and \( -6x \) is \( 3x \).
\[
3x^{2} - 6x = 3x(x - 2) = 0
\]
**Step 2: Apply the Zero Product Property.**
If \( AB = 0 \), then either \( A = 0 \) or \( B = 0 \).
\[
3x = 0 \quad \text{or} \quad x - 2 = 0
\]
**Step 3: Solve for \( x \).**
\[
x = 0 \quad \text{or} \quad x = 2
\]
**Solution:** \( x = 0 \) and \( x = 2 \)
---
### **b) \( x^{2} - 81 = 0 \)**
**Step 1: Recognize the difference of squares.**
\[
x^{2} - 81 = x^{2} - 9^{2} = (x - 9)(x + 9) = 0
\]
**Step 2: Apply the Zero Product Property.**
\[
x - 9 = 0 \quad \text{or} \quad x + 9 = 0
\]
**Step 3: Solve for \( x \).**
\[
x = 9 \quad \text{or} \quad x = -9
\]
**Solution:** \( x = 9 \) and \( x = -9 \)
---
### **c) \( x^{2} - x = 12 \)**
**Step 1: Bring all terms to one side to set the equation to zero.**
\[
x^{2} - x - 12 = 0
\]
**Step 2: Factor the quadratic equation.**
We need two numbers that multiply to \(-12\) and add to \(-1\).
\[
(x - 4)(x + 3) = 0
\]
**Step 3: Apply the Zero Product Property.**
\[
x - 4 = 0 \quad \text{or} \quad x + 3 = 0
\]
**Step 4: Solve for \( x \).**
\[
x = 4 \quad \text{or} \quad x = -3
\]
**Solution:** \( x = 4 \) and \( x = -3 \)
---
### **d) \( x(x - 9) = -14 \)**
**Step 1: Expand and bring all terms to one side.**
\[
x^{2} - 9x + 14 = 0
\]
**Step 2: Factor the quadratic equation.**
We need two numbers that multiply to \(+14\) and add to \(-9\).
\[
(x - 7)(x - 2) = 0
\]
**Step 3: Apply the Zero Product Property.**
\[
x - 7 = 0 \quad \text{or} \quad x - 2 = 0
\]
**Step 4: Solve for \( x \).**
\[
x = 7 \quad \text{or} \quad x = 2
\]
**Solution:** \( x = 7 \) and \( x = 2 \)
---
### **e) \( 3x^{\frac{2}{3}} - 7x^{\frac{1}{3}} + 2 = 0 \)**
**Step 1: Make a substitution to simplify the equation.**
Let \( y = x^{\frac{1}{3}} \). Then \( y^{2} = x^{\frac{2}{3}} \).
Substitute into the equation:
\[
3y^{2} - 7y + 2 = 0
\]
**Step 2: Factor the quadratic in \( y \).**
We need two numbers that multiply to \(3 \times 2 = 6\) and add to \(-7\).
\[
3y^{2} - 6y - y + 2 = 0 \\
3y(y - 2) -1(y - 2) = (3y - 1)(y - 2) = 0
\]
**Step 3: Apply the Zero Product Property.**
\[
3y - 1 = 0 \quad \text{or} \quad y - 2 = 0
\]
**Step 4: Solve for \( y \).**
\[
y = \frac{1}{3} \quad \text{or} \quad y = 2
\]
**Step 5: Substitute back \( y = x^{\frac{1}{3}} \) and solve for \( x \).**
- For \( y = \frac{1}{3} \):
\[
x^{\frac{1}{3}} = \frac{1}{3} \\
x = \left( \frac{1}{3} \right)^{3} = \frac{1}{27}
\]
- For \( y = 2 \):
\[
x^{\frac{1}{3}} = 2 \\
x = 2^{3} = 8
\]
**Solution:** \( x = \frac{1}{27} \) and \( x = 8 \)
---
### **f) \( x - 3x^{\frac{1}{2}} - 4 = 0 \)**
**Step 1: Make a substitution to simplify the equation.**
Let \( y = x^{\frac{1}{2}} \) (which means \( y = \sqrt{x} \)). Then \( y^{2} = x \).
Substitute into the equation:
\[
y^{2} - 3y - 4 = 0
\]
**Step 2: Factor the quadratic in \( y \).**
We need two numbers that multiply to \(-4\) and add to \(-3\).
\[
(y - 4)(y + 1) = 0
\]
**Step 3: Apply the Zero Product Property.**
\[
y - 4 = 0 \quad \text{or} \quad y + 1 = 0
\]
**Step 4: Solve for \( y \).**
\[
y = 4 \quad \text{or} \quad y = -1
\]
**Step 5: Substitute back \( y = \sqrt{x} \) and solve for \( x \).**
- For \( y = 4 \):
\[
\sqrt{x} = 4 \\
x = 16
\]
- For \( y = -1 \):
\[
\sqrt{x} = -1
\]
Since \( \sqrt{x} \) represents the principal (non-negative) square root, \( \sqrt{x} = -1 \) has no real solution.
**Solution:** \( x = 16 \)
---
**Summary of Solutions:**
- **a)** \( x = 0 \) and \( x = 2 \)
- **b)** \( x = 9 \) and \( x = -9 \)
- **c)** \( x = 4 \) and \( x = -3 \)
- **d)** \( x = 7 \) and \( x = 2 \)
- **e)** \( x = \frac{1}{27} \) and \( x = 8 \)
- **f)** \( x = 16 \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución